Geostrategic Analysis of the Current Situation in the Southeastern Mediterranean: The Case of the Geostrategic Position of Greece and the Issue of “Diplomatic Time”. - Ioannis Mazis (Defensor Pacis, 2005)
The post Arafat era of the Palestinian issue is characterized by two different possible paths: 1) The path of conflict between opposite groups of PLO, i.e. Hamas (which is more widely accepted by people than Fatah), Hezbollah as well as other “Arafatian” tendencies which will lead the Palestinian case to disaster, and 2) The desired path of finding a “successor” to Arafat, who will be accepted as a negotiator by the other side that is the Israeli and, principally, the American one. In that case, acceptance by the American side is far more important than that by the Israeli government, as it will help address the Palestinian claims more fully. As things have evolved according to what was predicted, Mahmoud Abbas (better known under his PLO name as Abu Mazen) is Arafat’s successor and is considered by the Israelis as a tough but honest negotiator; he is also accepted by the Americans. Certainly, in both cases, it is reasonable that diplomatic references between the two parties will be defined in the Oslo Agreement Ι and ΙΙ and in the “Road Map”, since the aforementioned Agreement has been accepted by i) the American arbitration and the Quartet ii) the Israeli side and iii) the Palestinian side. Moreover, iv) it bears the seal of Arafat, which provides the text with moral and political vindication for the Palestinians and, therefore, with greater flexibility for legitimate national maneuvers to his successor. In both cases, the period within which commonly accepted conclusions may be reached, can be no less than 5 years.